HUBUNGAN MOTIVASI PERAWAT DENGAN KESESUAIAN PENGISIAN NATIONAL INSTITUTES OF HEALTH STROKE SCALE (NIHSS) DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Fitria, Nurul; Suroso, Jebul (NHM PRESS, 2025)
The NIHSS (National Institutes of Health Stroke Scale) used a quantification method to determine stroke sensitivity as 0.71-0.90, with a mean correlation between stroke sensitivity and neurological assessment. The study aimed to identify clinically significant patients who were diagnosed with the NIHSS method and to identify patients with stroke. The study aims to provide information and motivation for patients with the NIHSS stroke assessment and to conduct a stroke assessment at the RSUD stroke Center Prof. Dr. Margono Soekarjo Purwokerto. This method of drilling involves drilling in a certain quantity using cross-sectional drilling. The population and sample of penitent children is estimated at 35 people using the sensible method. The statistics used are Chi-square. This index shows the Chi-square mean motivation and overall NIHSS pension assessment with a mean value of 0.858 and a significance level of 0.000. The mean mean value of the NIHSS mean value assessment was 0.718 with a significance level of 0.000 or lower from the alpha level (α = 0.05). The method used to determine the amount of money spent on the room is as follows: if the calculation can be done with a high degree of accuracy, the player who is also interested will be able to calculate the amount and motivation for the calculation in the table, so the NIHSS assessment will be carried out quickly.